Identification and analysis of genes causing varietal differences of cesium accumulation in soybean: Soybean genes for varietal Cs difference. Issue 6 (2nd November 2021) - Uda, Shingo; Fukuhara, Izumi; Daniela, Artigas Ramírez María; Kojima, Katsuhiro; Djedidi, Salem; Agake, Shin-Ichiro; Kaga, Akito; Matsunami, Hisaya; Moriyama, Hiromitsu; Yamada, Tetsuya; Yokoyama, Tadashi; Ohkama-Ohtsu, Naoko
ABSTRACT: Here, we explored the genomic loci and genes responsible for differences in Cs accumulation in the seeds of two soybean ( Glycine max (L.) Merr.) cultivars, namely 'Enrei' (high accumulator) and 'Onihadaka' (low accumulator), using quantitative trait loci (QTL)-seq. For analysis, F3 and F5 generations were generated by crossing the two cultivars followed by self-fertilization. In the putative QTL regions of the F3 generation, Glyma.11G099100 annotated as the vacuolar sorting protein/ubiquitin receptor VPS23 was found. VPS23A regulates the salt overly sensitive (SOS) signaling cascade in Arabidopsis, and mutations in SOS2 reduce radiocesium accumulation in rice grains. In the putative QTL regions of the F5 generation, Glyma.06G112200, which is a homolog of the usually multiple acids move in and out transporter (UMAMIT) proteins in Arabidopsis, was found. UMAMIT proteins are the exporters of amino acids, and the addition of cysteine or its derivative methyl cysteine to the growth medium increased Cs accumulation in A. thaliana . Both Glyma.11G099100 and Glyma.06G112200 carried polymorphisms – an amino acid substitution – between 'Enrei' and 'Onihadaka.' Yeast cells heterologously expressing the Onihadaka-type Glyma.06G112200 showed higher Cs accumulation than those expressing the Enrei-type. Yeast cells expressing the Enrei-type Glyma.06G112200 showed lower Cs accumulation than the vector controls; however, there was no significant difference between yeast cells expressing the Onihadaka-type and the vector controls. These results suggest that variations in the sequences of Glyma.11G099100 and Glyma.06G112200 in 'Enrei' and 'Onihadaka' are possibly responsible for differences in Cs uptake between these soybean cultivars.